Patient preferences using telehealth during the COVID‐19 pandemic in four Victorian tertiary hospital services. - Rasmussen, Bodil; Perry, Rachel; Hickey, Martha; Hua, Xinyang; Wong, Zee Wan; Guy, Lauren; Hitch, Danielle; Hiscock, Harriet; Dalziel, Kim; Winter, Naomi; Maier, Andrea B. (Internal Medicine Journal, 2022)
Background: The Coronavirus disease 2019 (COVID‐19) pandemic has had a major impact on healthcare services with many changes to telehealth care delivery. More information is needed about the patient perspective of telehealth in hospital services and the potential costs and benefits for patients. Aim: To measure patients' evaluation of telehealth, preferences for telehealth versus in‐person appointments, and potential cost savings by patient characteristics. Methods: A cross‐sectional online survey (including patient and appointment characteristics, telehealth evaluation, preferences for care and costs) of adult patients using video telehealth in four metropolitan tertiary hospital services in Melbourne, Victoria. Results: A total of 1045 patients (median age 44 years; interquartile range 29–59) participated with an overall response rate of 9.2%. For 98.7% patients, telehealth was convenient, 96.4% stated that it saved time, 95.9% found telehealth acceptable to receive care and 97.0% found that telehealth improved their access to care. Most (62.6%) preferred in‐person consultations, although 86.9% agreed that telehealth was equivalent to an in‐person consultation. Those in regional and rural areas were less likely to prefer in‐person consultations. Patients attending for medical reasons were less likely to prefer in‐person consultation compared with patients with surgical reasons. Patient preference to telehealth was independent of level of education, appointment type, self‐rated health status and socio economic status. Patients saved an average of A$120.9 (standard deviation A$93.0) per appointment, with greater cost savings for patients from low and middle socio economic areas and regional or rural areas. Conclusion: Telehealth video consultations were largely evaluated positively with most patients considering the service to be as good as in‐person. Understanding patient preference is critical to consider when implementing telehealth as mainstream across hospital health services.